2013
DOI: 10.1007/s00704-013-0894-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of data homogenization on estimate of temperature trend: a case of Huairou station in Beijing Municipality

Abstract: Daily minimum temperature (Tmin) and maximum temperature (Tmax) data of Huairou station in Beijing from 1960 to 2008 are examined and adjusted for inhomogeneities by applying the data of two nearby reference stations. Urban effects on the linear trends of the original and adjusted temperature series are estimated and compared. Results show that relocations of station cause obvious discontinuities in the data series, and one of the discontinuities for Tmin are highly significant when the station was moved from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…The urbanization effects on the annual mean Tmin and Tmax trends were statistically insignificant [20.018C (10 yr) 21 and 20.048C (10 yr) 21 , respectively] for the original data series, but they reached 0.398C (10 yr) 21 and 0.108C (10 yr) 21 , respectively, for the inhomogeneity-adjusted data series (Zhang et al 2013). When the adjustments are made more thorough, however, the increase in urban warming effect will be substantial.…”
Section: The Current State Of Observationsmentioning
confidence: 97%
See 3 more Smart Citations
“…The urbanization effects on the annual mean Tmin and Tmax trends were statistically insignificant [20.018C (10 yr) 21 and 20.048C (10 yr) 21 , respectively] for the original data series, but they reached 0.398C (10 yr) 21 and 0.108C (10 yr) 21 , respectively, for the inhomogeneity-adjusted data series (Zhang et al 2013). When the adjustments are made more thorough, however, the increase in urban warming effect will be substantial.…”
Section: The Current State Of Observationsmentioning
confidence: 97%
“…Various approaches were utilized for the detection and adjustment of the data inhomogeneities (e.g., Peterson et al 1998;Yan et al 2001;Li et al 2004b;Ren et al 2005;Moberg and Jones 2005). It was also found in studies of SAT change in mainland China using homogenized SAT data Zhou and Ren 2005;Zhang et al 2013;Li et al 2014). The adjustments for inhomogeneities, however, were generally to remedy the ''breakpoints'' in the SAT data series arising from relocations, and to rectify the pre-breakpoint data series against those from the present locations.…”
Section: The Current State Of Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, previous studies have shown a clear division in temperature trends between large cities and neighboring rural areas (e.g. Stone, 2007;McCarthy et al, 2010;Ren and Zhou, 2014;Zhang et al, 2014). This underlines the need to quantify the degree to which background temperature trends are amplified by urbanization.…”
Section: Introductionmentioning
confidence: 91%